Comparative Fiber Morphology of Four Underutilized Native Tree Species in Maguindanao, Philippines: 10.32526/ennrj/23/20240311 - Villareal, Jayric F.; Untong, Rafael U.; Mispil, Anisa U.; Poclis, Cindy E.; Numeron, Charry Mae S.; Marasigan, Oliver S. (Environment and Natural Resources Journal, 2025)
The focus of this study was to characterize and compare the fiber morphology (fiber length, fiber diameter, lumen diameter, cell wall thickness, and cell wall fraction) and derived values (Runkel ratio, slenderness ratio, flexibility ratio, Mulhsteph ratio, rigidity coefficient, and Luce’s shape factor) of four underutilized native tree species grown in the Maguindanao region, namely; Dita (Alstonia scholaris (L.) R. Br.), Himbabao (Broussonetia luzonica Blanco), Tangisang Bayawak (Ficus variegata Blume), and Kalukoi (Ficus callosa Willd.). Wood samples from the selected trees (between 10-20 years old) were collected at dbh level (1.30 m) and then macerated for three hours. The macerated wood fibers were observed under a Euromex compound microscope and then measured using ImageJ Software. Results revealed that F. variegata had the longest recorded fiber (2.73 mm) with the thickest cell wall (9.57 µm) and highest values for cell wall fraction (36.72%), Runkel ratio (0.74), slenderness ratio (60.48), Mulhsteph ratio (53.63%), rigidity coefficient (0.17), and Luce’s shape factor (0.43). As for fiber diameter, F. callosa (52.83 µm) was largest. Moreover, A. scholaris fibers recorded the largest lumen diameter (38.73 µm) with the highest flexibility ratio (77.74%). Analysis of variance showed significant differences relative to fiber morphology and their derived values, except for slenderness ratio. Results suggested that the four underutilized species are good not only for pulp and paper production, but also have potential for light construction, wooden toys and shoes, pencil slats, matchsticks, toothpicks, ice cream spoons, popsicle sticks, boxes, shelves, molding, veneer and plywood, buoys, and floats. In further validation of the suitability of materials towards intended uses, characterization of other wood properties (e.g., physical and mechanical) and consideration of factors like genetic control, locations/habitats, stand density, elevation, age and diameter classes, height level and wood types are recommended.